2017
DOI: 10.1039/c6cp07700e
|View full text |Cite
|
Sign up to set email alerts
|

Toward accurately modeling N-methylated cyclic peptides

Abstract: Cyclic peptides have unique properties and can target protein surfaces specifically and potently. N-Methylation provides a promising way to further optimize the pharmacokinetic and structural profiles of cyclic peptides. The capability to accurately model structures adopted by N-methylated cyclic peptides would facilitate rational design of this interesting and useful class of molecules. We apply molecular dynamics simulations with advanced enhanced sampling methods to efficiently characterize the structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“… 32 Also other force-field-based studies applying enhanced sampling techniques, such as metadynamics 33 , 34 and replica-exchange MD, 35 to characterize the structural ensemble of cyclic peptides showed highly promising results. 36 38 …”
Section: Introductionmentioning
confidence: 99%
“… 32 Also other force-field-based studies applying enhanced sampling techniques, such as metadynamics 33 , 34 and replica-exchange MD, 35 to characterize the structural ensemble of cyclic peptides showed highly promising results. 36 38 …”
Section: Introductionmentioning
confidence: 99%
“…We found that for small CPs, two dihedral angles, either the f and j angles of the same residue (f i and j i ) or the j angle of one residue and the f angle of the next residue (j i and f iþ1 ), need to change coherently to enable conformational switches. By targeting these essential transitional motions using bias-exchange metadynamics (BE-META) simulations, we can efficiently sample the conformational space of a CP (22)(23)(24). Using this method, we started examining CP sequence-structure relationships with explicit-water molecular dynamics (MD) simulations by gradually substituting Gly residues in cyclo-(GGGGGG) with Val.…”
Section: Introductionmentioning
confidence: 99%
“…One of these template structures, cyclo‐(aAAAAA) (underlines indicate N ‐methylated residues), contained all trans peptide bonds and two type II β‐turns at residues 6 Aa 1 and 3 AA 4 in DMSO (Figure A). When simulated with explicit DMSO molecules, the simulation results accurately recapitulated the NMR structure (Figure B) . However, this is not the case when simulated with implicit solvent using a dielectric constant equivalent to DMSO ( ɛ = 47) (Figure C).…”
Section: Computational Design Of Cyclic Peptidesmentioning
confidence: 87%
“…Therefore, it remains to be tested whether RSFF2 can successfully predict solution structures of CPs, or those CPs containing cis peptide bonds and/or non‐natural amino acids. In a recent study, it was shown that RSFF2 was not capable of reliably predicting the cis / trans isomers of simple N ‐methylated cyclic hexapeptides . Further optimization of the force field to describe the ratio between the cis and trans conformations is thus required if de novo structure prediction including the cis / trans isomer state is desired.…”
Section: Computational Design Of Cyclic Peptidesmentioning
confidence: 99%